Seroprevalence and trends of hepatitis B virus, hepatitis C virus and human immunodeficiency virus in Syrian blood donors at Damascus University Blood Center between 2004 and 2021 - Alassad, Alia; Al Rahwanji, Mhd Jawad; Yousfan, Amal; Al Moualem, Sally; Farhat, Arwa; Youssef, Lama A. (Frontiers in Public Health, 2023)
Introduction Seroprevalence of transfusion-transmitted viral infections (TTVIs) is a valuable indicator for assessing blood safety, population health and health system performance in the times of peace and conflicts. Only scarce information is available on the impact of the decade-long violent conflict on the prevalence of TTVIs in Syria. Moreover, hepatitis B vaccine was introduced to the national vaccination program in 1993; however, no data is available on the vaccine effectiveness. Methods In this retrospective cross-sectional study, we compiled the screening results for major TTVIs, namely hepatitis B virus (HBV), hepatitis C virus (HCV), and human immuno-deficiency virus (HIV), of volunteer donors at Damascus University Blood Center from May 2004 to October 2021. Prevalence was expressed in percentages for the entire study group and subgroups. Chi-square test and linear regression were used to examine the differences and describe trends in prevalence, respectively, based on demographic characteristics (i.e., age and gender) and time. P-value of <0.005 was considered statistically significant. Results Of the total 307,774 donors (82.27% males, median age 27 years), 5,929 (1.93%) had serological evidence of at least one TTVI, and 26 (0.0085%) had multiple infections. The lowest prevalence (1.09%) was detected in donors aged 18–25 years old, and a higher prevalence (2.05%) was evident in males in comparison with females (1.38%). The seroprevalence of HBV, HCV, and HIV was 1.18, 0.52, and 0.23%, respectively. Trend analyses revealed a significant regression in HBV and HIV prevalence from 2011 to 2021. HBV seropositivity depicted a temporal decline by 80%, from 0.79% in 2011 to 0.16% in 2021 in those born in 1993 and thereafter. Discussion The seroprevalence of HBV, HIV, and to a lesser extent HCV dropped over the study 18-year period. Possible explanations may include implementation of the HBV vaccine, robust national health system, conservative sociocultural values, and isolation.